2021
DOI: 10.1186/s40623-021-01364-w
|View full text |Cite
|
Sign up to set email alerts
|

Observing Earth’s magnetic environment with the GRACE-FO mission

Abstract: The Gravity Recovery and Climate Experiment Follow-On (GRACE-FO) mission carries magnetometers that are dedicated to enhance the satellite’s navigation. After appropriate calibration and characterisation of artificial magnetic disturbances, these observations are valuable assets to characterise the natural variability of Earth’s magnetic field. We describe the data pre-processing, the calibration, and characterisation strategy against a high-precision magnetic field model applied to the GRACE-FO magnetic data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 52 publications
(64 reference statements)
2
23
0
Order By: Relevance
“…In Antarctic regions close to the magnetic pole where the vertical magnetic field exceeds − 52, 974 nT, the magnetic data are saturated and have been flagged and discarded from the further analysis. The 12-bit digitization of the GRACE magnetometer data result in increased noise when analysing the data: the quantization noise produced by a N = 12-bit digitizer sampling in steps of size d results in a root-mean-squared (rms) noise (Schwartz 1980…”
Section: The Grace Magnetometer Measurementsmentioning
confidence: 99%
“…In Antarctic regions close to the magnetic pole where the vertical magnetic field exceeds − 52, 974 nT, the magnetic data are saturated and have been flagged and discarded from the further analysis. The 12-bit digitization of the GRACE magnetometer data result in increased noise when analysing the data: the quantization noise produced by a N = 12-bit digitizer sampling in steps of size d results in a root-mean-squared (rms) noise (Schwartz 1980…”
Section: The Grace Magnetometer Measurementsmentioning
confidence: 99%
“…As part of the attitude and orbit control system, the GRACE-FO mission carries magnetometers that aim to enhance the satellite's navigation. Stolle et al (2021) performed detailed calibration of the magnetic measurements from GRACE-FO. They showed that during times of geomagnetically quiet conditions, the mean magnetic residual to the geomagnetic model CHAOS-7 (Finlay et al 2020) is around 1 nT with standard deviations below 10 nT, which is remarkably good for a nonscience instrument.…”
Section: Grace-fo Mission and The Magnetic Measurementsmentioning
confidence: 99%
“…It confirms that after an appropriate calibration and characterization of artificial magnetic disturbances, the magnetic observations of GRACE-FO are valuable assets to investigate the natural variability of Earth's magnetic field. Details about the calibration and initial validation of GRACE-FO magnetic data are given in Stolle et al (2021).…”
Section: Grace-fo Mission and The Magnetic Measurementsmentioning
confidence: 99%
“…Together with other missions in this post-VAP era, the NextSat-1/ISSS can contribute useful information on the radiation belt to the space science community. In addition to the particle and cold plasma observations described above, magnetic field data from the onboard FGM are being calibrated by empirical geomagnetic field models, following Olsen et al (2020) and Stolle et al (2021). As soon as the calibration is finished, the magnetic field data will also be made available to the public.…”
Section: Accepted Articlementioning
confidence: 99%